Pengelolahan Citra Digital Dalam Mengukur Kemiringan Menggunakan Metode Trigonometri Dan Numerik - Liza nurpatmala; ardi wijaya (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
A house is a basic human need as a place of activity, shelter, and rest. One of the problems that is often overlooked in house construction is the mismatch or slope in the size of the room. Wall misalignment due to inaccurate measurements can affect building comfort and safety. This research uses technological advances in room slope measurement with trigonometric and numerical methods. The results show that the trigonometric and numerical methods have precision, recall, and accuracy rates reaching 100%. This method is effective and reliable for measuring the slope based on the captured digital image, ensuring that the measurements taken are true and accurate.